Feeding Preferences of Grass Carp (Ctenopharyngodon idella ) for Three Aquatic Plants - Abdullah‎, Jennan Najim; Taher‎, Majid Maki; Al-Dubakel, Adel Yacop (Journal of Kerbala for Agricultural Sciences, 2020)
The present study was conducted to determine the feeding preferences of grass carp (Ctenopharyngodon idella) for three aquatic plants i.e. Water fern (Azolla filiculoides), duckweed (Lemna spp.) and water hyssop (Bacopa monnieri), in two different water temperature (22-24 and 27-29 oC ) for the period from 30 Oct.2019 to 12 Dec. 2019. Water hyssop were neglected from the second temperature experiment since no plant consumed in the first trail. The average fish weight in 22 -24 oC was 91.85±12.59 and in 27-29 oC was 89.19±16.18. Mean daily feeding rates (DFR) consumption of grass carp from water fern and duckweed were not significantly different (P>0.05), but both plants were eaten in significantly (P<0.05) greater quantities than water hyssop plant which was not eaten by grass carp. The consumed plants were 48.00 and 39.77% BW/day from water fern and duckweed in temperature 22-24 oC, while in 27-29 oC it was 47.19 and 41.83 %BW/day respectively. It was concluded from the present study that grass carp equally prefer water fern and duckweed but not water hyssop; this may be associated with the nature of taste and leave structure.